Spectral Characteristics of Needle Array-Plate Dielectric Barrier Discharge Plasma and Its Activated Water - Yibing Li (Hindawi Limited, 2021)
The plasma-activated water (PAW), as a new environmentally friendly nonthermal processing technology, has attracted wide attention for its applications in agriculture, food, and biomedical fields. This paper used the needle array-plate dielectric barrier discharge (needle array-plate DBD) device to activate deionized water and prepare PAW simply and efficiently. It was found that the concentration of reactive oxygen and nitrogen species (RONS) generated in the process of needle array-plate DBD was large and varied. Especially in the wavelength range of 600–770 nm, the spectral intensity is stronger. And, the ionic wind is more likely to interact with the deionized water. The changes in PAW parameters and UV/Vis spectra with treatment time were measured under different voltages and needle-dielectric plate distances. Results show that increasing discharge voltage or decreasing needle-dielectric plate distance increases the concentration of RONS, ionic wind speed, water evaporation, and conductivity of the PAW and decreases pH. UV/Vis spectra results show that prolonged treatment time results in increased total absorbance and concentrations of H2O2 and NO3− and that a new absorption peak appears at 210 nm in the UV/Vis spectra. When the wavelength is larger than 210 nm, a redshifted new peak and color enhancement are observed. The seeds of Astragalus adsurgens Pall were treated by discharge plasma, PAW, and the combination of plasma and PAW. It was found that high voltage and long-time activated PAW could significantly increase the ROS level of seeds and seedlings after germination for 3 days, resulting in oxidative stress damage. The survival rate of seeds was lower than that under the half lethal dose. This paper provides a feasible device design for treating activated water in large quantities with high efficiency, which is important for the application of PAW and mutation breeding of A. adsurgens Pall.